New Zealand journal of research in performing arts and education : nga mahi a rehia - Drama New Zealand (Organization); University of Canterbury (Drama New Zealand in association with the University of Canterbury, 2008)
Peer-reviewed academic e-journal published by Drama New Zealand in association with the University of Canterbury. Articles address issues concerning the performing arts and education in New Zealand. All articles available in full-text.
Keywords: Performing arts : New Zealand : Periodicals; Arts in education : New Zealand : Periodicals; Performing arts : Study and teaching (Higher) : New Zealand; Arts du spectacle : Nouvelle-Zélande : Périodiques; Arts en éducation : Nouvelle-Zélande : Périodiques; Arts in education; Performing arts; Performing arts : Study and teaching (Higher); New Zealand